PENGARUH KEPRIBADIAN DAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR TERHADAP KINERJA PEGAWAI DINAS PERTANAHAN KOTA PALOPO - Asdar, Muh; Kasran, Muhammad; Dewi, Sari Ratna (ITB AAS Indonesia Surakarta, 2025)
The purpose of this study is to examine how employee performance in the Department of Palopo City Land is influenced by personality and organizational citizenship behavior. In order to address research questions and test the hypotheses that have been developed, this study employs a quantitative methodology that focuses on data collection and statistical analysis. The 40 individuals that participated in this study were all Palopo City Land Service personnel. The saturated sample approach was the sampling strategy employed, resulting in 40 current employees serving as research participants. Primary data collected by distributing questionnaires to respondents was used in the data collection process. Every question on the survey is assigned a Likert scale score, which ranges from 1 to 5. Use of the SPSS program was used to analyze the data. The findings demonstrated that employee performance is positively and significantly impacted by organizational citizenship behavior and personality